‘School’s Out, But Class’s on’: Experiences of Foreign Teachers Teaching EFL Online in China during the COVID-19 Lockdown - Nicholas Vorster Fouche; Maglin Moodley (Institut Agama Islam Negeri Palopo, 2022)
Education the world over has experienced the impact of COVID-19 on the various aspects in teaching and learning. In China, the Ministry of Education started a campaign called the School’s Out, But Class’s on campaign. The majority of schools migrated from face-to-face teaching to online teaching during the nationwide lockdown. Both local Chinese teachers as well as foreign teachers teaching EFL in China experienced a range of challenges during the migration to online teaching. This study focused exclusively on foreign teachers who taught EFL in China during the COVID-19 lockdown. A mixed methods research approach was used, which saw data being collected from a sample of foreign EFL teachers from four western countries. These participants responded to an online survey and an in-depth interview regarding their teaching experiences during the COVID-19 lockdown in Guangdong, China. The results of this study indicated that majority of the participants had a negative experience regarding online teaching in China. This negative experience was greatly attributed to the lack of training and support they as foreign teachers received in China. The results further highlighted the challenges foreign teachers experienced with regards to culture and adopting cultural norms of Chinese society. Recommendations from this study, include a review of training of EFL teachers by institutions to accommodate issues around culture and cultural norms and finally the training of EFL teachers in using the different learning management systems located within the educational space.